2G waste lignin to fuel and high value-added chemicals: Approaches, challenges and future outlook for sustainable development. (April 2021) - Sivagurunathan, P.; Raj, Tirath; Mohanta, Chandra Sekhar; Semwal, Surbhi; Satlewal, Alok; Gupta, Ravi P.; Puri, Suresh K.; Ramakumar, S.S.V.; Kumar, Ravindra
Abstract: Lignin is produced as a byproduct in cellulosic biorefinery as well in pulp and paper industries and has the potential for the synthesis of a variety of phenolics chemicals, biodegradable polymers, and high value-added chemicals surrogate to conventional petro-based fuels. Therefore, in this critical review, we emphasize the possible scenario for lignin isolation, transformation into value addition chemicals/materials for the economic viability of current biorefineries. Additionally, this review covers the chemical structure of lignocellulosic biomass/lignin, worldwide availability of lignin and describe various thermochemical (homogeneous/heterogeneous base/acid-catalyzed depolymerization, oxidative, hydrogenolysis etc.) and biotechnological developments for the production of bio-based low molecular weight phenolics, i.e. polyhydroxyalkanoates, vanillin, adipic acid, lipids etc. Besides, some functional chemicals applications, lignin-formaldehyde ion exchange resin, electrochemical and production of few targeted chemicals are also elaborated. Finally, we examine the challenges, opportunities and prospects way forward related to lignin valorization. Graphical abstract: Image 1 Highlights: 2G Lignin as a bio-based biorefineries platform for highly advanced products preparation. Thermocatalytic and biotechnological approaches were emphasized for lignin value addition. Thermo catalytic approach is an effective process for lignin valorization in bulk scale. In biological valorization, adipic acid production is promising towards scale-up.